Impact of location decision on supply chain performance : a cross country comparison. - Phua, Yue Cheng. (2010)
The competition to attract multinational companies to locate manufacturing plants has always been intense among ASEAN countries given the enormous benefits that such investments yield. In order to attract multinational companies, there is a need to understand the criteria that multinational companies use to determine the most appropriate location. It is important to note that a firm does not work in isolation to deliver a particular product to the final customer. The decision of where to locate a manufacturing plant has an impact on the performance of the entire supply chain. While there is much research in the areas of plant location decision and supply chain management, there is little research that tries to link these two issues together. This research attempts to explore empirically the relationship between location and supply chain performance.